Low-Dose Valganciclovir Prophylaxis Is Safe and Cost-Saving in CMV-Seropositive Kidney Transplant Recipients. (December 2021) - Shi, Yiyun; Lerner, Alexis Hope; Rogers, Ralph; Vieira, Kendra; Merhi, Basma; Mecadon, Krista; Osband, Adena J.; Bayliss, George; Gohh, Reginald; Morrissey, Paul; Farmakiotis, Dimitrios
Introduction: Observational studies suggest that low-dose valganciclovir prophylaxis (450 mg daily for normal renal function) is as effective as and perhaps safer than standard-dose valganciclovir (900 mg daily) in preventing CMV infection among kidney transplant recipients. However, this practice is not supported by current guidelines due to concerns for breakthrough infection from resistant CMV, mainly in high-risk CMV donor-seropositive/recipient-seronegative kidney transplant recipients. Standard-dose valganciclovir is costly and possibly associated with higher incidence of neutropenia and BKV DNAemia. Our institution adopted low-dose valganciclovir prophylaxis for intermediate-risk (seropositive) kidney transplant recipients in January 2018.Research Question: To analyze the efficacy (CMV DNAemia), safety (BK virus DNAemia, neutropenia, graft loss, and death), and cost savings associated with this change.Design: We retrospectively compared the above outcomes between CMV-seropositive kidney transplant recipients who received low-dose and standard-dose valganciclovir, transplanted within our institution, between 1/19/2014 and 7/15/2019, using propensity score-adjusted competing risk analyses. We also compared cost estimates between the two dosing regimens, for 3 months of prophylaxis, and for different percentage of patient-weeks with normal renal function, using the current average wholesale price of valganciclovir.Results: We studied 179 CMV-seropositive kidney transplant recipients, of whom 55 received low-dose and 124 standard-dose valganciclovir. The majority received nonlymphocyte depleting induction (basiliximab). Low-dose valganciclovir was at least as effective and safe as, and more cost-saving than standard-dose valganciclovir.Conclusion: This single-center study contributes to mounting evidence for future guidelines to be adjusted in favor of low-dose valganciclovir prophylaxis in CMV-seropositive kidney transplant recipients.